PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PERAWAT RUMAH SAKIT UNIVERSITAS TANJUNGPURA - Admin, Fitriani Sakdiah B1021151004 (Jurnal Manajemen Update, 2020)
This study aims to examine and analyze the Effect of Compensation and Work Environment on Job Satisfaction of Nurses at Tanjungpura University Hospital. This research is motivated by complaints from several nurses at Tanjungpura University Hospital regarding compensation issues and the work environment they feel. Some of the complaints they felt were salary of honorary nurses not in accordance with the Pontianak City Regional Minimum Wage, fees for services that were erratic and discharged schedules, and a work environment where the air temperature was uncomfortable and a bit noisy.     This type of research is a causal study with a quantitative approach to test the influence between variables, where hypothesis testing uses descriptive statistical analysis, multiple linear regression analysis, classic assumption tests and research instrument tests. This research was conducted at Tanjungpura University Hospital with a period of 5 months. Research data were collected by distributing questionnaires and interviews. The research sample consisted of 111 nurses using the census method.     The results showed that compensation and work environment had a positive and significant effect on job satisfaction. The results of data processing using SPSS 25 show that the data is reliable, normal, linear, and does not occur multiceriarity and heterokedesity. The ability of the independent variable in explaining its effect on the job satisfaction variable is 62.2%, while the rest is explained by other variables outside the research model.     Researchers suggest the Tanjungpura University Hospital to pay more attention to the welfare of nurses, especially in the field of compensation and work environment. Service fees must be issued regularly and scheduled each month and the Tanjungpura University Hospital is expected to also be able to provide Air Conditioners in the nurses' workspaces.Keywords: compensation, work environment and job satisfaction.DAFTAR PUSTAKAAkhmad, J. (2013), Manajemen Sumber Daya Manusia. Jakarta: Lentera Ilmu        Cendikia Akhwanul, A., & Taminil. (2015). Pengaruh Kompensasi TerhadaP Kepuasan        Kerja Karyawan Gaya Makmur Mobil Medan. Jurnal Bisnis Administrasi,      04 (2), 59-68. Aruan, Q. S., & Fakhri, M. (2015). Pengaruh Lingkungan Kerja Terhadap   Kepuasan Kerja Karyawan Lapangan Departemen Grasberg Power  Distribution PT. Freeport Indonesia. MODUS, 27 (2), 141-162. Aprilandi. (2015). Pengaruh Pengawasan, Kompensasi dan Promosi Terhadap        Kepuasan Kerja  Karyawan Pada PT. Swakarya Insan Mandiri Pekanbaru.        Jom FEKON 2 (2), 1-15. Bagus, D. (2009). Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja.     Diakses dari http://jurnal-sdm.blogspot.com/2009/04/faktor-faktor-yang          mempengaruhi.html. Darmadi, H. (2014). Metode Penelitian Pendidikan dan Sosial. Bandung:    Alfabeta. Dwijayanti, M. N., Dewi, A. A., & Sagung, K. (2015). Pengaruh Kompensasi dan             Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada    Perusahaan Daerah Air Minum Tirta Mangutama Bandung. E-Jurnal            Manajemen Unud, 4 (12), 4274-4301. Ghozali, I. (2016). Aplikasi Analisis Multivariate dengan Program IBM SPSS 23. Semarang:BPFE UNDIP. Hasibuan, M. (2013). Manajemen Sumber Daya Manusia. Jakarta: PT Bumi           Aksara. Karimah, I. (2017). Perbandingan Tingkat Kepuasan Kerja Perawat Rumah           Sakit Pemerintah dan Rumah Sakit Swasta Di Kota Makassar, Universitas              Islam Negeri Alauddin Makassar, Indonesia. Kuncoro, M. (2011). Metode Kuantitatif. Yogyakarta: YKPN Lumentut, M. D., & Dotulong, L. O. (2015). Pengaruh Motivasi,Disiplin, dan        Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Bank    Sulut Cabang Airmadidi. JURNAL EMBA, 3 (1), 74-85. Mangkunegara, A. P. (2011).Perencanaan dan Pengembangan Sumber Daya        manusia. Bandung: Rafika Aditama. Maxmanroe. (2019). Kepuasan Kerja: Pengertian, Indikator, Fungsi, dan Aspek                 Aspeknya 2019. Diakses dari https://www.maxmanroe.com/vid/karir/ Kepuasan kerja.html. Rino, M. (2016). Studi Komparatif Analisis Hubungan Motivasi Dengan     Kepuasan Kerja Perawat Pns dan Non Pns Serta Faktor ? Faktor      Determinannya di       Rsud Raden Mattaher Jambi, Universitas Andalas,   Indonesia. Rumengan, J. (2011). Metodelogi Penelitian dengan SPSS. Batam: UNIBA            PRESS.Sangadji, E. M., & Sopiah. (2010).Pendekatan Praktis dalam Penelitian.                             Malang: CV Andi Offset. Ida, S. P. (2018). Tinjauan Siyasah Dusturiyah Terhadap Pembinaan dan    Pengawasan Penyelenggaraan Pemerintah Daerah Menurut Peraturan      Pemerintah Nomor 12 Tahun 2017 (Studi Kasus Inspektorat Daerah           Kabupaten Purwakarta), Universitas Islam Negeri Sunan Gunung Jati,   Indonesia. Sedarmayanti. (2013). Manajemen Sumber Daya Manusia. Bandung: CV. Mondar            Maju. Simamora, B. (2005). Analisis Multivariat Pemasaran. Jakarta:Gramedia. Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung:            Alfabeta. Sunyoto, D. (2012), Manajemen Sumber Daya Manusia, Jakarta: CAPS Sutrisno, E., (2011), Manajemen Sumber Daya Manusia, Jakarta :Prenada Media   Group   Wibowo, M., Musadieq, M.A., & Nurtjahjono, G. E. (2014). Pengaruh       Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Karyawan Pt.Telekomunikasi Indonesia Tbk. Kandatel Malang).Jurnal             Administrasi Bisnis 16 (1), 1-9.